Investigation of AR and VR Technologies in Plant Physiology Education: Assessment of Student Motivation and Preliminary Comprehension - Aulia Afza; Diana Susanti; Nursyahra Nursyahra; Mourend Devegi; Bambang Supriatno; Riandi Riandi; Lince Meriko (Balai Publikasi Indonesia, 2026)
Plant Physiology Education often faces challenges in visualizing complex internal and conceptual processes, such as photosynthesis, transpiration, and mineral nutrition. Traditional teaching methods often fail to motivate students and facilitate in-depth understanding. Investigation of AR and VR Technologies in Plant Physiology Education. This study employed a quantitative methodology with a descriptive design and correlational analysis, involving 50 students who completed a questionnaire regarding their motivation and comprehension of interactive digital books utilizing Augmented Reality (AR) and Virtual Reality (VR). The findings indicated a substantial enhancement in students' motivation and comprehension following the utilization of this technology. The Pearson correlation test indicated a positive link between students' motivation and comprehension, with a significance level of p-value <0.01. The t-test further validated a significant disparity in students' motivation and comprehension when utilizing AR and VR. This technology facilitates a more dynamic and immersive learning experience, aiding students in comprehending complex principles of plant physiology that are challenging to grasp through traditional techniques. This study advocates for the utilization of augmented reality (AR) and virtual reality (VR) technologies to enhance the quality of education in biology, particularly in the area of plant physiology